Problematika Eksistensi Sarang Burung Walet : Tinjauan Hukum dan Kebijakan - Siti Sahra Nggiu; Mutia CH. Thalib; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses the Problems of the Existence of Swallow's Nests and the procedures and permits for their establishment in Gorontalo Regency. The method used in the research is empirical, with qualitative descriptive data analysis that describes and describes data and field facts.The results of the research show that the problems with the existence of swallow nests in Gorontalo Regency consist of; Neighbors' rights were not fulfilled when the building was erected, because the swallowtail bird's nest building, apart from being erected without the permission of the closest neighbors, was also located right near a residential area. The noise from recorded bird calls can disrupt people's activities, and the presence of bird nests does not rule out the possibility of carrying various types of diseases. The lack of permit processing, where the construction of swallow nests in the Gorontalo Regency area has not yet fully obtained a building permit, because for the construction of swallow nests there were no proposals received by the government. Triggering conflict, where it is feared that building swiftlet nests could develop bird flu, cause odors caused by swiftlet feces, the smell of rubbish used as additional food for swiftlets, disrupt air quality, and pollute residents' reservoir water. Apart from that, this conflict can occur because the owner of the swallow's nest building is not domiciled on the premises, so it becomes a problem in itself. The construction of swallow's nests in Gorontalo Regency does not comply with the procedures and permits for establishment as stated in the Decree of the Minister of Home Affairs Number 71 of 1999 concerning Guidelines for the Management and Business of Swallow's Nests, where Chapter III Article 4 is managed with the permission of the Regional Head. Apart from that, it is not yet based on Law Number 28 of 2009 regarding Regional Taxes and Retributions, as well as Regional Regulation No. 5 of 2020 concerning Swallow's Nest Tax in Gorontalo Regency. This is due to weak awareness of environmental law, the community does not understand the procedures for establishing wallet bird nests and local government outreach has not been optimal.